Physiology of Rhodophiala bifi da germination. (FAVE Sección Ciencias Agrarias, 2021)
Our aim is to contribute to the knowledge of the basic physiological characteristics of the germination and perdurability of Rodophiala biﬁda seeds. The effect of different temperatures, presence / absence of light, two years of harvest and one of storage, on the ﬁnal percentage of seminal states was evaluated. By adjusting the germination percentage as a function of time, the following were estimated: Maximum Percentage, Average Time and Germination Uniformity. The seeds showed neutral photoblastism, without dormancy or sanitary problems. Between 7 and 28 °C they exceeded 90 % of germination, in pregnancies and with one year of storage (good perdurability); at 33 °C it decreased by 10 % and coincided with the increase in dead and ﬁrm white seeds. Germination dynamics adjust to active function. With the Average Times in the range between 7 and 25 ° C, the Optimum Temperature (25 °C), Base (4.83 °C) and Thermal Time (1666 °Ch).
Keywords: Rhophiala bifida; germination; perdurability